Social Capital on Instagram: Application for Small Apparel Retailers - McKneely, Brittany R.; Kim, Jiyoung; Leung, Xi; Pookulangara, Sanjukta (Journal of Marketing Development and Competitiveness, 2020)
The purpose of this study is to investigate consumer’s perceived benefit and development of social capital in small apparel retailer’s Instagram pages that ultimately lead to purchase intentions for the retailer, applying Social Capital theory. Using a field survey method, 200 complete and accurate responses were collected and used to run multiple regression analysis. The result revealed several insignificant relationships, contrary to our initial expectation. The ad hoc multiple regression analysis found several other significant relationships between the social capital dimensions and perceived benefit dimensions on brand identification, trust, and purchase intentions.